Transient appearance of antegrade conduction via an AV accessory pathway caused by atrial fibrillation in a patient with intermittent Wolff-Parkinson-White syndrome. Issue 5 (1st May 2000) - Niwano, S; Kitano, Y; Moriguchi, M; Izumi, T
Abstract : A 55 year old man with intermittent Wolff-Parkinson-White (WPW) syndrome had an episode of atrial fibrillation (AF) that lasted for 117 days. After interruption of the AF a Δwave appeared that lasted for two days and then disappeared. Exercise stress and isoprenaline infusion could not reproduce the Δwave, but after another episode of AF which lasted for seven days a persistent Δwave appeared that lasted for six hours. In an electrophysiological study performed on a day without a Δwave, neither antegrade nor retrograde conduction via an accessory pathway was seen, but after atrial burst pacing (at 250 ms cycle length) for 10 minutes, a Δwave appeared lasting for 16 seconds. Atrial electrical remodelling—that is, the shortening of the atrial effective refractory period caused by AF, is a possible mechanism of the appearance of the Δwave.